2020
DOI: 10.1111/trf.15787
|View full text |Cite
|
Sign up to set email alerts
|

Bringing new plasma donors back: testing the efficacy of telephone and e‐mail communications with first‐time donors

Abstract: Australian governments fully fund the Australian Red Cross Blood Service for the provision of blood, blood products and services to the Australian community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…Previous research has predominately looked at the impact of telephone versus email when eliciting responses from donors. 18,26 Most of this literature has found that the combined effect of email plus a phone call is the preferred method for prompting return, but little to no differences have been found between phone and email. 18,26 Germain and colleagues 18 concluded that electronic reminders are preferred as they are more cost-effective.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has predominately looked at the impact of telephone versus email when eliciting responses from donors. 18,26 Most of this literature has found that the combined effect of email plus a phone call is the preferred method for prompting return, but little to no differences have been found between phone and email. 18,26 Germain and colleagues 18 concluded that electronic reminders are preferred as they are more cost-effective.…”
Section: Discussionmentioning
confidence: 99%
“…18,26 Most of this literature has found that the combined effect of email plus a phone call is the preferred method for prompting return, but little to no differences have been found between phone and email. 18,26 Germain and colleagues 18 concluded that electronic reminders are preferred as they are more cost-effective. The use of SMS has increased among BCAs, with previous research demonstrating the effectiveness of a postdonation SMS notifying donors of the location to which their blood has been dispatched.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were obtained by Duan et al (2020) , who determined CP as a promising rescue option for severe COVID-19 cases. Not only in line with these encouraging results, Thorpe et al (2020) noted that the demand for plasma-derived products has increased exponentially over the last ten years, fueling the attention that CP supply chains have been receiving. This emphasis is warranted, since there are multiple organizational challenges associated with the development and implementation of a CP program, including policies for testing and approving plasma donations ( Stanworth et al 2020 ).…”
Section: Literature Reviewmentioning
confidence: 56%
“…Strategies to improve blood donation have been a source of debate and study. With respect to plasma donations, telephone outreach from persons knowledgeable about the process have found significant efficacy, especially for recruiting first time donors [6]. Other studies on participation found phone calls to be superior to mail-in requests, and furthermore found 3 phone calls per patient to be the maximum number to generate meaningful benefit [7,8].…”
Section: Introductionmentioning
confidence: 99%